Kupas Tuntas Keterkaitan Film Jumbo dengan Komunikasi Interpersonal dan Peningkatan Kunjungan Bioskop - Vania Anindya Cahyono Putri; Muhammad Afzaal Parvez; Maulana Raya Rizky; Hira Choir Robbani; Nadiatus Sholihah; Arsih Amalia Chandra Permata; Wiyata Wiyata (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
This study aims to examine the relationship between the animated film Jumbo and interpersonal communication and its influence on increasing cinema visits in Indonesia. The Jumbo film raises the themes of friendship, bullying, courage, and adverse childhood experiences (ACEs). This is considered capable of building strong emotional resonance with the audience and increasing the audience's visits to the cinema as a place to watch. Through a descriptive qualitative approach with the content analysis method, the researcher examined the visual elements, dialogue, and storyline in the film. The results of the study show that the Jumbo film effectively represents interpersonal communication theory, such as symbolic interactionism and the concept of self-reflection that encourage empathy and shape the audience's self-perception and sociality. In addition, the visualization of the amusement park in the film triggers feelings of nostalgia as a tourism motivation with the support of digital marketing strategies and electronic word of mouth (eWOM) which have an impact on the spike in visits to the cinema. Jumbo is not only an entertainment medium, but also an effective cultural and tourism promotion tool. Thus, Jumbo proves that local animated works can shape cultural narratives and increase tourism motivation.